Streptomyces: The biofactory of secondary metabolites - Alam, Khorshed; Mazumder, Arpita; Sikdar, Suranjana; Zhao, Yi-Ming; Hao, Jinfang; Song, Chaoyi; Wang, Yanyan; Sarkar, Rajib; Islam, Saiful; Zhang, Youming; Li, Aiying (Frontiers in Microbiology, 2022)
Natural products derived from microorganisms serve as a vital resource of valuable pharmaceuticals and therapeutic agents. Streptomyces is the most ubiquitous bacterial genera in the environment with prolific capability to produce diverse and valuable natural products with significant biological activities in medicine, environments, food industries and agronomy sectors. However, a lot of natural products remain unexplored from Streptomyces. It is exigent to develop novel antibiotics, agrochemicals and anticancer medicines etc. due to the fast growth in resistance to antibiotics, cancer chemotherapeutics, and pesticides. This review article focused and discussed the natural products secreted by Streptomyces and its function and importance in curing human diseases and ailments. Moreover, we discussed genomic driven drug discovery strategies and also give a future perspective for drug development from the Streptomyces.